(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
The tannery solid waste (fleshing) was collected from Hazaribagh, Dhaka. It has been found that fleshing contains 82.57% volatile matter. Further characterization of fleshing showed that it contains low C/N ratio of 2.64 and high pH of 10.99. These characteristics were not suitable for using fleshing as a substrate for anaerobic digestion. The study has been carried out in different ratio of waste fleshing, domestic sewage and cow dung at total solid 6% concentration. In all the reactors fleshing and domestic sewage were mixed at 1:1 ratio. On the basis of the performance of the reactors it was evident that the reactor which contains 75% fleshing with domestic sewage and 25% cow dung showed optimum result. Under optimum condition volatile solids destruction 52%, specific gas production 0.476 L/g volatile solids feed and methane yield 73% were achieved. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22006 Bangladesh J. Sci. Ind. Res. 49(2), 119-124, 2014